Anemia is Associated with Bone Mineral Density in Chronic Obstructive Pulmonary Disease. (1st June 2013) - Rutten, Erica P.A.; Franssen, Frits M.E.; Spruit, Martijn A.; Wouters, Emiel F.M.
Abstract: Objective: Patients with chronic obstructive pulmonary disease (COPD) often suffer from systemic co-morbidities, including anemia. However, anemia is related to multiple outcomes in COPD and in other chronic diseases, but it's impact is underestimated in COPD. The objective of the present study was to relate anemia in patients with COPD with disease-related outcomes, systemic inflammation and COPD related co-morbidities. Methods: Data of 321 patients with COPD admitted for pulmonary rehabilitation were analysed. Besides general characteristics, lung function, body composition, arterial gases and plasma haemoglobin concentration, disease-related outcomes (health-related quality of life by St. George's Respiratory Questionnaire, 6-minute walking distance, mMRC dyspnea scale, and BODE index), systemic inflammation (C-reactive protein (CRP)) and self-reported and objectified co-morbidities (low muscle mass, osteoporosis, renal failure, risk for undernutrition) were taken into account. Results: First, 20% of the patients were anemic, and 8% was polycythemic. Polycythemic patients had a lower proportion of men and a lower proportion of low muscle mass compared to the other groups. Anemic patients had higher plasma CRP levels and lower total body bone mineral density compared to the other groups. There was no difference in disease-related outcomes or other co-morbidities in the patients with and without anemia. Even after adjustment for confounders, anemia was an independent determinant for higher CRP levels and lower bone mineral density. Conclusion: Anemia is frequently present in patients with COPD and there is evidence that it is associated with lower whole body bone mineral density.